Jurisprudence of Responsibility Male Guardianship as a Model (Journal of Imam Al-Kadhim College, 2025)
The fact that women share life’s matters with men does not mean that they are similar and equal in all aspects and effects of life. There is no single standard that indicates that men are equal in the same effects among themselves, despite their belonging to the category of masculinity and manhood. Therefore, piety may be one of the criteria for distinguishing between men and women, not masculinity and femininity. The Holy Quran did not neglect to show that they share in the human status, such as performing duties and bearing responsibility for actions. Since the foundation and origin of humanity is the soul, not the body, the result is that both of them, men and women, share in humanity, and they were created from one soul. Almighty Allah said: “O mankind, fear your Lord, who created you from one soul” [An-Nisa’: 1]. In another verse, Almighty Allah said: “And among His signs is that He created for you mates from among yourselves, that you may find tranquility in them and He has placed between you affection and mercy, indeed, in that, are signs for a people who give thought’’. (Ar-Rum 21) However, a man being characterized with intelligence and good management, their ability to endure the hardships of life, such as hard work, whether at work or in worship in obedience to Allah, in addition to their great determination, made men have the upper hand in leadership than women, as Almighty Allah said: {Men are in charge of women because Allah has given one more (strength) than the other and because they spend from their wealth.} [An-Nisa’ 4:34] From here we find that the family guardianship is borne by men for many reasons. The man’s bearing of life’s burdens and many other responsibilities may have considered as a part of the standard guardianship over women, which in turn have become closer to performing his social duty.
Keywords: Jurisprudence of Responsibility - Male Guardianship - wife's obedience- the problematic of Equality between men and women